2012
DOI: 10.1007/s11060-012-0801-z
|View full text |Cite
|
Sign up to set email alerts
|

A histopathological diagnostic marker for human spinal astrocytoma: expression of glial fibrillary acidic protein-δ

Abstract: Although histopathological diagnosis of spinal cord astrocytomas is important for postoperative treatment planning and prognosis, there is a lack of reliable immunohistochemical markers. The purpose of our study was to assess the expression pattern of GFAP-δ in spinal cord astrocytomas in human patients and to evaluate the utility of GFAP-δ as an immunohistochemical diagnostic marker. A total of 22 patients with spinal cord astrocytic tumors were included in this study. Patients were classified according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…Other studies have been suggested that human ependymomas arise from regionally distinct populations of radial glial cells [24,26], with abnormal GFAP-δ positive expression [15]. GFAP-δ increased significantly with tumor grade [27].…”
Section: Overall Comparisonsmentioning
confidence: 92%
See 4 more Smart Citations
“…Other studies have been suggested that human ependymomas arise from regionally distinct populations of radial glial cells [24,26], with abnormal GFAP-δ positive expression [15]. GFAP-δ increased significantly with tumor grade [27].…”
Section: Overall Comparisonsmentioning
confidence: 92%
“…Altogether, these results suggest that GFAP-δ and nestin could be clinically relevant markers associated with tumor invasiveness in cerebral astrocytomas as well as, with ependymomas. Heo DH, et al [12]. Observed that the optical density of GFAP-δ increased significantly with astrocytoma grade and suggest that GFAP-δ may be an additional, reliable histopathological diagnostic marker for spinal cord astrocytomas.…”
Section: Overall Comparisonsmentioning
confidence: 99%
See 3 more Smart Citations